Effect of six oximes on acutely anticholinesterase inhibitor-induced oxidative stress in rat plasma and brain - Antonijevic, Evica; Kotur-Stevuljevic, Jelena; Musilek, Kamil; Kosvancova, Andrea; Kuca, Kamil; Djukic-Cosic, Danijela; Spasojevic-Kalimanovska, Vesna; Antonijevic, Biljana (Archives of toxicology, 2018)
Beside the key inhibition of acetylcholinesterase (AChE), involvement of oxidative stress in organophosphate (OP)-induced toxicity has been supported by experimental and human studies. On the other hand, according to our best knowledge, possible antioxidant properties of oximes, the only causal antidotes to OP-inhibited AChE, have been examined only by a few studies. Thus, we have determined the effect of four conventional (obidoxime, trimedoxime, pralidoxime, asoxime) and two promising experimental oximes (K027, K203) on dichlorvos (DDVP)-induced oxidative changes in vivo. Wistar rats (5/group) were treated with oxime (5% LD50 i.m) immediately after DDVP challenge (75% LD50 s.c). Oxidative stress biomarkers were determined in plasma and brain 60 min after the treatment: prooxidative-superoxide anion (O2·-) and total oxidative status (TOS); antioxidative-superoxide dismutase (SOD), total thiol (SH) groups, total antioxidant status (TAS) and paraoxonase (PON1); tissue oxidative stress burden-prooxidative-antioxidative balance (PAB) and oxidative stress index (OSI); oxidative tissue damage-malondialdehyde (MDA) and advanced oxidation protein products (AOPP). All oximes were able to attenuate DDVP-induced oxidative stress in rat plasma and brain. Changes of determined parameters in brain were not as prominent as it was seen in plasma. Based on OSI, better abilities of oxime K027, K203 and obidoxime to maintain DDVP-induced oxidative stress in rat brain were shown as compared to trimedoxime, pralidoxime and asoxime. Oximes can influence the complex in vivo redox processes that might contribute to their overall therapeutic efficacy. Further research is needed to understand the underlying molecular mechanisms involved in this phenomenon.
Keywords: Organophosphate Poisoning; pyridinové sloučeniny; Rats; superoxiddismutasa; trimedoxim; Malondialdehyde; cholinesterasové inhibitory; malondialdehyd; obidoxim chlorid; Efficacy; Pralidoxime Compounds; Cholinesterase Inhibitors; mužské pohlaví; aryldialkylfosfatasa; Oxidative Stress; mozek; Oximes; Antioxidats; Obidoxime Chloride; krysa rodu Rattus; Pro-oxidants; Pyridinium Compounds; otrava organofosfáty; Superoxide Dismutase; Brain; Dichlorvos; zvířata; biologické markery; dichlorvos; pralidoximové sloučeniny; Oxime K027; Aryldialkylphosphatase; oxidační stres; Biomarkers; Oxime K203; Trimedoxime; oximy; Male; Animals